1997
DOI: 10.1007/s11627-997-0056-0
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of nitrate and phosphate salts, sucrose, and inoculum culture age on growth and sesquiterpene production in Artemisia annua hairy root cultures

Abstract: We analyzed four factors (phosphate and nitrate salts, sucrose, and culture inoculum age), simultaneously at three levels using a fractional factorial design method to determine the most suitable conditions for maximizing both root biomass and terpenoid production in transformed Artemis& annua root cultures. Optimal growth conditions were determined to be: nitrate (15 mM), phosphate (1.0 nrM), sucrose content (5% wt/vol), and inoculum age (8 d-old). Determination of optimal conditions for sesquiterpene product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 19 publications
(23 reference statements)
1
17
0
Order By: Relevance
“…The growth promoting effect of 4% sucrose level was also noted earlier in case of hairy root cultures of Artemisia annua 28 and Plumbago zeylanica.…”
supporting
confidence: 77%
“…The growth promoting effect of 4% sucrose level was also noted earlier in case of hairy root cultures of Artemisia annua 28 and Plumbago zeylanica.…”
supporting
confidence: 77%
“…Initially we used inoculum from late-log cultures (14 day) to compare biomass yields in flasks. However, previous studies with hairy root cultures showed that the age of the inoculum culture might affect root growth as well as secondary metabolite production (Takahashi et al 2001;Weathers et al 1996Weathers et al , 1997. A common result of polyploidy in plants is a reduced number of cell divisions during growth and development (Adaniya and Shira 2001;Otto and Whitton 2000), so overall reduced growth was not surprising.…”
Section: Growth Of Diploid and Tetraploid Clonesmentioning
confidence: 99%
“…Four factors: phosphate and nitrate salts, sucrose, and culture inoculum age were analyzed simultaneously to determine the most suitable conditions for maximizing both root biomass and sesquiterpene lactones production in transformed A. annua root cultures by Weathers et al (1997). The authors concluded that optimal growth conditions were determined to be: nitrate (15 mM), phosphate (1.0 mM), sucrose content (5% w/v), and inoculum age (8 day-old) whereas the determination of optimal conditions for sesquiterpene production was more complicated and did not provide the most effective solutions for maximizing the production of artemisinin.…”
Section: Effect Of Sucrose Nitrogen and Phosphatementioning
confidence: 99%